Synthesis and characterisation of nickel Schiff base complexes containing the meso-1, 2-diphenylethylenediamine moiety: selective interactions with a tetramolecular DNA quadruplex1. Issue 7 (21st February 2015) - Davis, Kimberley J.; Richardson, Christopher; Beck, Jennifer L.; Knowles, Brett M.; Guédin, Aurore; Mergny, Jean-Louis; Willis, Anthony C.; Ralph, Stephen F.
<x xml:space="preserve">Abstract</x> Two nickel(ii) Schiff base complexes exhibit binding selectivity for a tetramolecular DNA quadruplex.